High Risk Human Papillomavirus Persistence Among HIV-infected Young Women in South Africa. (April 2015) - Adler, David; Wallace, Melissa; Bennie, Thola; Abar, Beau; Sadeghi, Rokhsanna; Meiring, Tracy; Williamson, Anna-Lise; Bekker, Linda-Gail
Highlights: Persistence of infection with HR-HPV increases cervical cancer risk HIV+ young women had a seven-fold increased rate of HR-HPV persistence in our study HR-HPV testing may improve cervical cancer screening for HIV+ young women Summary: Objectives: Persistence of infection with high-risk Human papillomaviruses (HR-HPV) increases the risk of incident and progressive precancerous lesions of the cervix. Rates of HR-HPV persistence have been shown to be increased among HIV-infected adult women, however there is a paucity of literature addressing HPV persistence in the young HIV-infected population. We compared rates of HR-HPV persistence between HIV-infected and HIV-uninfected young women. Methods: We obtained self-collected vaginal swabs at six-month intervals from 50 HIV-uninfected and 33 HIV-infected young women recruited through a community youth center (age 17-21 years) and compared rates of HR-HPV persistence. HR-HPV testing was conducted using the Roche's Linear Array® HPV Test. Results: Eighty-three prevalent (upon baseline testing) and incident (upon subsequent testing) individual HR-HPV infections were identified among 43 members of the cohort (23 HIV-uninfected and 20 HIV-infected). At twelve months, 19% of baseline HR-HPV infections continued to be present with a statistically significant difference between HIV-uninfected and HIV-infected participants (4% versus 31%; p=0.01). Conclusions: HIV-infected young women in our cohort had a seven-fold increased rate of persistence of HR-HPV overall at 12 months, indicating an increased risk for incident and progressive precancerous lesions. Identification of persistent infection with HR-HPV may complement cytological findings in determining the need for colposcopy.